2014
DOI: 10.1177/1040638714550180
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of Besnoitia bennetti infection in donkeys (Equus asinus)

Abstract: Besnoitiosis is an emerging infectious disease of donkeys ( Equus asinus) in the United States for which there are currently no serologic methods of diagnosis. A study was performed to evaluate physical examination findings and 3 serologic assays for the detection of Besnoitia bennetti infection in donkeys. A prospective study of 416 donkeys from 6 privately owned herds across 5 U.S. states (New York, Pennsylvania, Vermont, Oregon, and Washington) was performed. Donkeys were examined for clinical lesions sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Similarly, in a study of equine besnoitiosis caused by B. bennetti, Ness et al. () recently reported the presence of Western blot seronegative animals with clinical signs. Moreover, previous authors showed that endemic bovine besnoitiosis involves a high percentage of unapparent infections related to fluctuations in antibody levels, clinical recoveries and barely detectable mild clinical signs that may lead to false‐negative results (Bigalke, ; Liénard et al., ).…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, in a study of equine besnoitiosis caused by B. bennetti, Ness et al. () recently reported the presence of Western blot seronegative animals with clinical signs. Moreover, previous authors showed that endemic bovine besnoitiosis involves a high percentage of unapparent infections related to fluctuations in antibody levels, clinical recoveries and barely detectable mild clinical signs that may lead to false‐negative results (Bigalke, ; Liénard et al., ).…”
Section: Discussionmentioning
confidence: 83%
“…cysts in donkeys [ 18 ]; the presence of cysts in the buccal mucosa has been rarely described [ 28 ]. Visualizing cysts in two (nares and scleral) or more locations correctly identified 83% of infected donkeys [ 16 ]. Serology is less invasive than histological examination and is a better choice for detection of subclinical infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum from a cow chronically infected with B. besnoiti was used as a positive control, whereas serum samples from uninfected cattle and donkeys were used as negative controls. Serum was considered positive when at least four out of ten bands of specific tachyzoites antigens (45, 40, 37, 34, 30, 27, 22, 17, 16 and 15 kDa) were observed [ 5 , 16 ]. Figure 4 shows the results of the western blot.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…were reported to affect both horses and donkeys. Besnoitiosis in equids, caused by Besnoitia bennetti, is considered an emerging disease of donkeys in the United States [1]. Besnoitia spp.…”
Section: Accepted Manuscriptmentioning
confidence: 99%